CLINICAL, LABORATORY AND ECHOCARDIOGRAPHIC LEFT ATRIAL APPENDAGE THROMBUS PREDICTORS IN PATIENTS WITH ATRIAL FIBRILLATION - Kalatsei, L. V.; Ibrahim, A.; Fernando, Ch. E. S. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2025)
Background. The most common and persistent arrhythmia today is atrial fibrillation (AF). Decrease in blood flow velocity in the left atrium appendage (LAA), endothelial dysfunction and hemostatic system changes can cause the development of left atrium appendage thrombosis (LAAT), which is the main source of thromboembolism in patients with AF. Numerous studies have explored various clinical, echocardiographic, and laboratory parameters as potential predictors, however, the predictive power of these parameters is still insufficient for real clinical practice. Objective of the study was to evaluate predictive ability of clinical, laboratory and echocardiographic markers in diagnosis of LAAT in patients with non-valvular AF. Material and methods. The study included 100 patients with persistent non-valvular AF who were admitted for direct current cardioversion. According to transesophageal echocardiography results, patients were divided into 2 groups: patients with LAA thrombus «LAAT» (n=30) and without LAA thrombus «Non LAAT» (n=70). Results. Patients with LAAT had a significantly longer duration period of persistent AF (7 [4; 9] months vs 4 [3; 6] months, p=0.004) in comparison with patients without LAAT. Laboratory markers of patients in both groups had no significant differences except for GFR (p=0.047) and NT-proBNP level (p=0.011). According to the results of echocardiography, patients didn’t have differences in left atrial (LA) diameter and volume (p>0.05). However, LA volume index was higher in patients with LAAT (p=0.007). When conducting a ROC analysis, the NT-proBNP level of ≥ 1689 pg/ml showed the largest area under the ROC curve (0.747) as well as the highest specificity (92.6%). Conclusions. Patients with LAAT had longer duration of persistent AF, higher values of LA volume index, as well as higher NT-proBNP levels. Further use of these parameters could help predict LAAT development in patients with AF.